Physiotherapists’ Experiences and Needs Regarding Pain Neuroscience Education in Switzerland: An Online Survey - Litzenburger, Alexandra; Fischer, Susanne (physioscience, 2025)
Almost 30 % of the population is affected by pain lasting longer than three months, and, out of those, every fourth person is in physiotherapeutic care. Pain Neuroscience Education (PNE) is an effective and low-priced tool for managing pain, wherein patients get taught about the neuroscience of pain, thus shifting their perspective. However, no studies have yet investigated whether physiotherapists actively integrate PNE into their practice in Switzerland, or whether there are unmet needs regarding PNE materials.Answer the research questions: Do Swiss physiotherapists know of and use PNE? What are limitations to the usage of PNE, and do physiotherapists have unmet needs regarding PNE materials?In this cross-sectional study, an online survey investigating the topic was sent to Swiss physiotherapists. Quantitative data were analysed using inferential statistics, and qualitative data using reflexive thematic analysis.Of the n = 358 participants, 61.5 % knew of PNE, 51.7 % utilised it, but only 39.4 % felt confident in applying it in their practice. The limitations most mentioned to usage were time and language barriers, while 24.0 % felt that they did not know PNE well enough. Indeed, only 21.0 % of the participants were taught PNE during their undergraduate studies, and specialised literature was only known to a fraction. Some felt new materials were needed, and the need for materials in a variety of languages was highlighted. Bridging the gap between knowing the neurophysiology of pain and teaching it to patients was an issue raised by several participants.Most physiotherapists of this sample in Switzerland know of PNE, but only a minority confidently utilises it in practice. Utilisation is limited by time constraints and language barriers and therapists struggle to transfer knowledge into practice. It is unclear whether new materials are needed, but techniques to teach patients definitely seem to be important.
Keywords: pain; pain neuroscience education; physiotherapy; chronic pain; undergraduate